PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA HOTEL MUTIARA MERDEKA PEKANBARU - Risnawati, Mitha; ", Suryalena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to determine how much influence the development of career and organizational commitment to employee performance at the Hotel Mutiara Merdeka Pekanbaru. Samples in this study as many as 52 respondents and techniques used Stratified Random Sampling. The data in this study using survey method through questionnaires filled by employees. Data obtained from the questionnaire and then processed to then tested by statistical SPSS. The results of analysis using simple linear regression analysis, multiple linear regression analysis, determination test (R2), individual significance test (t test), and simultaneous significant test (test F) so it can be seen that career development variables affect the employee performance variable, variable organizational commitment affect on employee performance, and career development variable, organizational commitment variable affect simultaneously to employee performance variable. Calculation result known R Square is coefficient of determination and obtained R Square vale equal to 0,471. Meaning career development and organizational commitment affect employee performance of 47,1%.Keywords: Career Development, Organizational Commitment, Employee Performance